Analysis of Progressive Muscle Relaxation on Psychophysiological Variables in Basketball Athletes - Battaglini, Marina Pavão [UNESP]; Pessôa Filho, Dalton Müller [UNESP]; Calais, Sandra Leal [UNESP]; Miyazaki, Maria Cristina Oliveira Santos; Neiva, Cassiano Merussi [UNESP]; Espada, Mário C.; de Moraes, Mayra Grava [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP] (MDPI, 2022)
The purpose of this study was to evaluate the effects of a progressive muscle relaxation program on psychological (stress levels, anxiety, and mood states) and physiological (blood pressure and heart rate) variables in basketball athletes. Fifty-nine basketball players, aged 14 to 19 years, and members of Bauru Basket team, were recruited for this study and grouped into control group (CG, n = 30) and intervention group (IG, n = 29). The participants were evaluated, before and after the intervention, by the following means: Competitive State Anxiety Inventory-2 (CSAI-2), to measure the pre-competitive anxiety state, i.e., how anxious each athlete felt just before the competition; Brunel Mood Scale (BRUMS), an instrument for early detection of overtraining syndrome; Recovery-Stress Questionnaire for Athletes (RESTQ-Sport), to identify the extent to which each athlete was physically or mentally stressed and the athlete’s current capability for recovery; Athlete Burnout Questionnaire (ABQ), specifically developed for athletes. The IG athletes participated in 12 progressive muscle relaxation sessions, a practice for tensing or tightening a specific muscle until an ideal state of relaxation is reached. Each participant had blood pressure and heart rate measured before and after every session. The CG athletes were evaluated similarly to those in the IG but without relaxation. The results showed statistically significant differences in cognitive anxiety (p = 0.039) and specific stress (p = 0.016) between CG and IG before the intervention; in addition, a significant heart rate decrease (p < 0.01) between IG and CG was noted.
Keywords: anxiety; athletes; blood pressure; heart hate; mood states; progressive muscle relaxation; stress